If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 4(1 + 7x) + -8(3x + -5) 16 = (1 * 4 + 7x * 4) + -8(3x + -5) 16 = (4 + 28x) + -8(3x + -5) Reorder the terms: 16 = 4 + 28x + -8(-5 + 3x) 16 = 4 + 28x + (-5 * -8 + 3x * -8) 16 = 4 + 28x + (40 + -24x) Reorder the terms: 16 = 4 + 40 + 28x + -24x Combine like terms: 4 + 40 = 44 16 = 44 + 28x + -24x Combine like terms: 28x + -24x = 4x 16 = 44 + 4x Solving 16 = 44 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 16 + -4x = 44 + 4x + -4x Combine like terms: 4x + -4x = 0 16 + -4x = 44 + 0 16 + -4x = 44 Add '-16' to each side of the equation. 16 + -16 + -4x = 44 + -16 Combine like terms: 16 + -16 = 0 0 + -4x = 44 + -16 -4x = 44 + -16 Combine like terms: 44 + -16 = 28 -4x = 28 Divide each side by '-4'. x = -7 Simplifying x = -7
| f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) | | 4-5-13-18+2= | | 14=8x+7-x | | 458000*9= | | ln(x-4)=6 | | 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 | | (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= | | 2b+3b-4b+3=17 | | 10y^3-11x^2+2-12y^3-13x^2= | | -82=-2(6-5r) | | 18y^2-18x^3+2-18y^4-18x^5= | | 5(3x+7)-11=54 | | (-8)(-2)= | | 5+4p-8p=-19 | | 14y^3-4x^2+2-6y^3-2x^2= | | x^2+10x+-4=0 |